Relationship Between Ginger Herbal Therapy Provision To Mothers Pregnancy Trimester 1 With Nausea And Vomiting Pregnancy Period - Mardiani Purba (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Introduction: Pregnancy is a natural process that can change the body, both physically and mentally. This results in complaints of nausea and vomiting. Nausea and vomiting are normal or common symptoms during the first trimester of pregnancy. This sometimes occurs in the morning, but can also occur during the day or night. Therapy that can be used to overcome complaints of nausea and vomiting is ginger therapy. This study aims to determine the relationship between the provision of ginger herbal therapy and nausea and vomiting in pregnant women in the first trimester. Method: This study used the Quasy Experiment method. The study population was all pregnant women in the first trimester at the Kasih Bunda Pratama Clinic. The sample in this study was 29 pregnant women. Data analysis used the testchi square. Results and Discussion: The results of the analysis obtained p value = 0.001 (p <0.05), this shows that there is a significant relationship between the provision of ginger herbal therapy and the reduction of nausea and vomiting in pregnant women in the first trimester. Conclusion: Ginger herbal therapy has the ability to reduce the frequency of nausea and vomiting in pregnant women in the first trimester. Herbal therapy and ginger can also be an alternative to overcome nausea and vomiting in pregnant women in the first trimester.